Transfer of technology (ToT) document of polyimide binder resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan. N. N.; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhansekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (2009)

Transfer of technology (ToT) document of ethyl silicate-32 - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of Technology (ToT)/ Technical Documents, 2011)

Transfer of technology (ToT) document of phenol-aniline-formaldehyde (sf-342a) resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of technology (ToT) document, 2011)

Thermotropic liquid crystalline polyesters derived from bis-(4-hydroxybenzoyloxy)-2-methyl-1,4-benzene and aliphatic dicarboxylic acid chlorides - Mulani, Khudbudin Baban; Momin, Mohasin Shamshuddin; Ganjave, Nitin V.; Chavan, Nayaku (Bulletin of Materials Science, 2015)
A series of thermotropic liquid crystalline polyesters derived from bis-(4-hydroxybenzoyloxy)-2-methyl-1,4-benzene(BHBOMB) and aliphatic dicarboxylic acid chlorides were investigated. All these polyesters were synthesized by interfacial polycondensation method and characterized by differential scanning calorimetry and wide-angle X-ray diffractometer. These polyesters consist of BHBOMB as a mesogenic diol and aliphatic diacid chlorides were used as flexible spacers. The length of oligomethylene units in polymer was varied from the trimethylene to the dodecamethylene groups. The transition temperatures and thermodynamic properties were studied for all these polymers. All these polyesters were soluble in chlorinated solvents such as chloroform, dichloromethane, dichloroethane, etc. More importantly, all these polyesters exhibited very large mesophase stability.
Keywords: dicarboxylic acid chloride; interfacial polycondensation; Liquid crystalline polyesters; rigid diol; thermotropic